2012
DOI: 10.1583/11-3627.1
|View full text |Cite
|
Sign up to set email alerts
|

Nitinol Stent Implantation vs. Balloon Angioplasty for Lesions in the Superficial Femoral and Proximal Popliteal Arteries of Patients With Claudication: Three-Year Follow-up From the RESILIENT Randomized Trial

Abstract: In this multicenter trial, primary implantation of a nitinol stent for moderate-length lesions in the femoropopliteal segment of patients with claudication was associated with better long-term results vs. balloon angioplasty alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
171
2
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(199 citation statements)
references
References 27 publications
17
171
2
9
Order By: Relevance
“…To date, there remains no clear-cut de facto gold therapy for endovascular applications in the lower limb with the best outcomes that we can apply to most if not all our patients who present with symptomatic lower limb disease (Table). Current data from numerous trials at various lengths of outcome duration (ranging from 12 to 60 months) [2][3][4][5][6][7][8][9][10][11][12][13] have shown that there remains a consistent but steady decline in primary patency with all devices over time. There has been a robust interest in what should be the default therapy for lower extremity disease.…”
mentioning
confidence: 99%
“…To date, there remains no clear-cut de facto gold therapy for endovascular applications in the lower limb with the best outcomes that we can apply to most if not all our patients who present with symptomatic lower limb disease (Table). Current data from numerous trials at various lengths of outcome duration (ranging from 12 to 60 months) [2][3][4][5][6][7][8][9][10][11][12][13] have shown that there remains a consistent but steady decline in primary patency with all devices over time. There has been a robust interest in what should be the default therapy for lower extremity disease.…”
mentioning
confidence: 99%
“…The reduced need for stenting has distinct advantages. Although stenting improves patency compared with PTA, [18][19][20][21] TLR rate has remained high on follow-up ranging from 19 to 37% 18,19,22,23 at 1 year and up to 49% at 2 years. 20 The main mechanism of reducing restenosis with stenting is the reduction of elastic recoil and negative remodeling with no impact on SMC proliferation.…”
mentioning
confidence: 99%
“…Based on a systematic literature review of clinical measures 17 , 12 publications including registries and clinical trials were used to estimate the TLR rates associated with each endovascular procedure studied [19][20][21][22][23][24][25][26][27][28][29]. More detailed information about TLR probabilities indicated in each study is shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%